ESTIMATION OF EFFICIENCY OF OPERATING SYSTEM OF TAX PLANNING IN THE COMMERCIAL ORGANIZATIONS - Evgeniy A. Samsonov (Статистика и экономика)
Present clause is devoted to scientific judgement and estimations of efficiency of stimulating mechanisms (tools) of application of system of tax planning in the commercial organizations which allow to estimate разнонаправленное influence of taxes on final financial result of the organization, and also to predict change of business activity of the organization depending on tax loading. The big attention is given to complicated questions of features of management by the taxation and the order of reflection in the tax account of the facts of the economic activities arising between the state, on the one hand, and managing subjects - the commercial organizations - with another.